Effects of cognitive behaviour therapy for anxiety and depression in children's and adolescents' post-disaster: A systematic review - Mawaddah Mawaddah; Budi Anna Keliat; Yudi Ariesta Chandra; Yossie Susanti Eka Putri (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Disasters are still one of the major phenomena that occur in Indonesia. In the period of February 2024, there were 173 disasters that hit the territory of Indonesia. Natural cause enormous physical and economic destruction, as well as many lives lost. Another impact of disasters is psychosocial problems, such as anxiety and depression. Anxiety and depression can be experienced by various populations. The most vulnerable population is adolescents. Purpose: To analyse the effects of cognitive behaviour therapy for anxiety and depression in children's and adolescents' post-disaster Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Children and adolescents post-disaster, I: Cognitive Behaviour Therapy (CBT), C: No therapy or standard care, O: Reduction in anxiety and depression, and S: Randomized controlled trial. The article search was conducted systematically using the keywords: “Cognitive Behaviour Therapy” OR “CBT” AND “Anxiety” AND “Depression” AND “Children” AND “Adolescent” AND “Disaster”. Results: A review of eight articles showed that Cognitive Behaviour Therapy is effective in reducing anxiety and depression in children and adolescents post-disaster. Compared to other therapies, CBT demonstrates a higher level of effectiveness, including in its modified and developed forms. Its application, when conducted following general procedures while considering cultural aspects and individual characteristics, yields significant results in psychological recovery. Conclusion: Cognitive Behavioral Therapy (CBT) has been shown to be effective in overcoming anxiety and depression in children and adolescents after disasters, with a better level of effectiveness than other therapies, including in modified forms. The application of CBT that considers cultural aspects and individual characteristics can significantly improve therapy outcomes.